2009
DOI: 10.1021/jf900786e
|View full text |Cite
|
Sign up to set email alerts
|

Lentils (Lens culinaris Medikus Subspecies culinaris): A Whole Food for Increased Iron and Zinc Intake

Abstract: Micronutrient malnutrition, the hidden hunger, affects more than 40% of the world's population, and a majority of them are in South and South East Asia and Africa. This study was carried out to determine the potential for iron (Fe) and zinc (Zn) biofortification of lentils ( Lens culinaris Medikus subsp. culinaris ) to improve human nutrition. Lentils are a common and quick-cooking nutritious staple pulse in many developing countries. We analyzed the total Fe and Zn concentrations of 19 lentil genotypes grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
3
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(123 citation statements)
references
References 26 publications
5
109
3
6
Order By: Relevance
“…Screening of more than 1,600 lentil accessions, including breeding lines, landraces and wild relatives, found that mineral content ranged from 23 to 95 ppm for zinc, and 42 to 132 ppm for iron [118,119,120,121,122].…”
Section: Zinc and Iron Lentilmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening of more than 1,600 lentil accessions, including breeding lines, landraces and wild relatives, found that mineral content ranged from 23 to 95 ppm for zinc, and 42 to 132 ppm for iron [118,119,120,121,122].…”
Section: Zinc and Iron Lentilmentioning
confidence: 99%
“…Mineral accumulation of zinc and iron in lentil seeds is influenced by environmental factors such as temperature, soil type, and fertility status [119,121,125,126,127]. Multi-location GxE testing is used to identify advanced lines and varieties with stable highmineral content across different environments and crop seasons.…”
Section: Zinc and Iron Lentilmentioning
confidence: 99%
“…Lentils are combined with the carbohydrate staples rice and wheat, forming a complete protein diet . Lentil has the potential to reduce micronutrient (iron and zinc) deficiency though the consumption of 100 g daily (Thavarajah et al, 2009). Additionally, lentil is a promising source of antioxidant phenolics and could serve as a dietary supplement (Zou et al, 2011).…”
Section: Crop Lentil (Lens Culinaris Medik)mentioning
confidence: 99%
“…Variation in seed nutrition may be due to genotype, market class (seed size, color), and the growing environment and may also be enhanced by premarket processing such as size sorting, dehulling, or splitting [5,6], or milling [7,8]. SigniWcant genetic variation in Fe and Zn concentrations with low concentrations of phytic acid (PA) is being reported in various crops, including pulses [3,4,6,9].…”
Section: Introductionmentioning
confidence: 99%